Emphysematous Pyelonephritis and Concurrent Emphysematous Osteomyelitis - Farha Ahmed Karlath; Mohamad Al Kateb; Richard Ellison (Annals of Internal Medicine: Clinical Cases)
We present a rare case of emphysematous pyelonephritis complicated by secondary emphysematous osteomyelitis, likely resulting from the hematogenous spread of Escherichia coli in a patient with multiple comorbid conditions. Early identification of computed tomography findings and prompt initiation of therapy resulted in a favorable outcome. This case underscores the importance of rapid diagnosis and intervention in patients with complex comorbid conditions, because early treatment can significantly improve outcomes.